CONSEQUENCES OF PARTICIPATING ARE IN UNTRADITIONAL RELIGIOUS ORGANIZATIONS (NRO) - Богдановський, І. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the basic socially and psychological consequences of entry of people are examined to untraditional religious organizations (NRO). The methods of rehabilitation of former members of NRO are examined, in fact submissive submission of adherents entails substantial changes group norms and rules in their personality.